The negociated Nordic labour markets: from bust to boom. Background paper for the conference on "The Nordic model: solution for continental Europe's problems?", Center for European Studies, Harvard University, May 9-10, 2008 - Dølvik, Jon Erik (Cambridge, MA, 2008)
"This paper provides an overview of the negotiated Nordic labor market regimes and their vari-ous paths of adjustment from bust to boom in recent decades. Developed in small, open econo-mies, the Nordic labor regimes are often associated with strong centralized agreements and asso-ciations, high union density, and extensive worker representation, which have been embedded in social models based on close interaction between working life policies, the welfare state and macroeconomic policies. In leaner forms these features have undoubtedly contributed to the high Nordic levels of mobility, equality and employment in recent years ("flexicurity"), but an often overlooked part of the story is the increased scope for product market competition and the supply-side reforms undertaken in the Nordic countries since the crises in the 1980-90s. Another distinction of the revitalized Nordic models is the growing importance of management-union negotiations and dialogue at the company level. A key argument in this paper is thus that the capacity for negotiated flexibility and adjustment in Nordic labor markets has been critically reli-ant on the multilevel, single-channel pattern of articulation between centralized coordination and decentralized negotiations linking restructuring, training, productivity and pay issues."